2004
DOI: 10.1016/j.ijgo.2004.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with inadequate prenatal care in Ecuadorian women

Abstract: Although prenatal care at our institution is free, adequacy was thought to be low. The main factors associated with poor prenatal care were mostly conditions related to poverty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
61
1
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 23 publications
14
61
1
9
Order By: Relevance
“…According to studies, higher parity among children has emerged as a barrier to adequately use ANC [18,[22][23][24][25][26], whereas high parity women tended to use the service more often than primiparous women [27], Similarly, studies found that women's first ANC visit was earlier in higher parity women in India [20].…”
Section: Survey Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…According to studies, higher parity among children has emerged as a barrier to adequately use ANC [18,[22][23][24][25][26], whereas high parity women tended to use the service more often than primiparous women [27], Similarly, studies found that women's first ANC visit was earlier in higher parity women in India [20].…”
Section: Survey Of Literaturementioning
confidence: 99%
“…According to some study, Place of residence was a statistically significant factor for adopting and continuing ANC. Pregnant women from urban areas used ANC more than their rural counterpart [22,24,30]. Women in urban areas were more likely to use antenatal care from a healthcare professional in Ethiopia [27].…”
Section: Survey Of Literaturementioning
confidence: 99%
“…Verificou-se que a mediana de idade das participantes esteve em 24 [20][21][22][23][24][25][26][27][28][29][30] …”
Section: Resultsunclassified
“…Resultados: selecionaram-se 248 mulheres, distribuídas em controle (n=161) e tabagistas durante a gestação (n=87). Verificou-se que a mediana de idade foi 24 [20][21][22][23][24][25][26][27][28][29][30] anos e a escolaridade 9 [7, anos. A maioria das mulheres (71,4%) realizou mais de seis consultas pré-natais.…”
Section: Introductionunclassified
See 1 more Smart Citation